Comparing Beerkan infiltration tests with rainfall simulation experiments for hydraulic characterization of a sandy‐loam soil. Issue 20 (17th August 2017) - Di Prima, Simone; Bagarello, Vincenzo; Lassabatere, Laurent; Angulo‐Jaramillo, Rafael; Bautista, Inmaculada; Burguet, Maria; Cerdà, Artemi; Iovino, Massimo; Prosdocimi, Massimo
Abstract: Saturated soil hydraulic conductivity, K s, data collected by ponding infiltrometer methods and usual experimental procedures could be unusable for interpreting field hydrological processes and particularly rainfall infiltration. The K s values determined by an infiltrometer experiment carried out by applying water at a relatively large distance from the soil surface could however be more appropriate to explain surface runoff generation phenomena during intense rainfall events. In this study, a link between rainfall simulation and ponding infiltrometer experiments was established for a sandy‐loam soil. The height of water pouring for the infiltrometer run was chosen, establishing a similarity between the gravitational potential energy of the applied water, E p, and the rainfall kinetic energy, E k . To test the soundness of this procedure, the soil was sampled with the Beerkan estimation of soil transfer parameters procedure of soil hydraulic characterization and two heights of water pouring (0.03 m, i.e., usual procedure, and 0.34 m, yielding E p  =  E k ). Then, a comparison between experimental steady‐state infiltration rates, i sR, measured with rainfall simulation experiments determining runoff production and K s values for the two water pouring heights was carried out in order to discriminate between theoretically possible ( i sR  ≥  K s ) and impossible ( i sR  <  K s ) situations. Physically possible K s values were only obtained by applying water at a relatively large distance from the soil surface, because i sR was equal to 20.0 mm h −1 and K s values were 146.2–163.9 and 15.2–18.7 mm h −1 for a height of water pouring of 0.03 and 0.34 m, respectively. This result suggested the consistency between Beerkan runs with a high height of water pouring and rainfall simulator experiments. Soil compaction and mechanical aggregate breakdown were the most plausible physical mechanisms determining reduction of K s with height. This study demonstrated that the height from which water is poured onto the soil surface is a key parameter in infiltrometer experiments and can be adapted to mimic the effect of high intensity rain on soil hydraulic properties.